CARTOON-based educational intervention for children to foster hygiene knowledge and emotional resilience in preschool children: a randomized controlled trial - Philipp Steinbauer; Magdalena Bichler; Renate Fuiko; Sanja Seferagic; Hanna Haas; Tamara Lisy; Sophie Weinmüller; Angelika Berger; Monika Olischar; Agnes Panagl; Vito Giordano (Frontiers in Pediatrics)
BackgroundIn the last four years, COVID-19 has prompted concerns about children's well-being. While children's physical health may not be severely affected, their psychological well-being is a significant concern. Therefore, we developed an interdisciplinary psychoeducational intervention program for children named CARTOON. The study aimed to assess whether CARTOON helps kindergarten children to better adhere to mandatory hygiene measures, while also investigating its potential to reduce children's anxiety.MethodsA randomized controlled trial was conducted from January and June 2021 in two Viennese kindergartens involving 53 children aged 3–6 years. Children were randomized into an intervention (specific psychoeducational program) and a control group (routine hygiene practices). CARTOON comprised five sessions covering key hygiene and COVID-19 awareness aspects, facilitated by trained staff. Primary outcomes included changes in children's emotional state and knowledge about COVID-19 and hygiene measures. Secondary outcomes assessed CARTOON's long-term impact on knowledge retention and emotional well-being.ResultsChildren in the intervention group showed increased COVID-19 knowledge from baseline to long-term assessment (3.9 ± 2.4 vs. 5.9 ± 2.0, p = .003). Moreover, children in the intervention group demonstrated significantly improved long-term hygiene knowledge compared to baseline (8.2 ± 2.2 vs. 5.9 ± 2.3, p < 0.001). Additionally, anxiety scores significantly decreased in the intervention group post-intervention compared to baseline (2.2 ± 1.7 vs. 5.6 ± 2.5; p = .01). Regression analysis identified higher age, higher maternal education, and lower family mental stress as knowledge acquisition predictors.ConclusionsOur findings demonstrate the efficacy of our psycho-educational program in enhancing both knowledge about COVID-19 and adherence to hygiene measures among preschool children, while also reducing anxiety related to the pandemic.Clinical Trial Registrationhttps://clinicaltrials.gov/ct2/show/NCT04724616.